ASPEK HUKUM PERTANGGUNGJAWABAN BANK ATAS HILANGNYA BENDA BERHARGA MILIK NASABAH YANG DISIMPAN DALAM SAFE DEPOSIT BOX (SDB) DAN UPAYA PENYELESAIANNYA - Rahmi Rahmi Zubaedah; Imanudin Imanudin Affandi; Dede Suana Ependi (TAHKIM, 2022)
The purpose of this study is to determine the factors that cause the loss of valuable objects belonging to customers stored in the Safe Deposit Box (SDB), to determine the bank's responsibility for the loss of valuable objects belonging to customers stored in the Safe deposit box (SDB) and to find out the efforts made by the customer for the loss of valuable objects stored in the Safe deposit box (SDB). The approach method used in this research is a normative juridical approach. That is the study of theories, concepts, legal principles and laws and regulations related to Safe Deposit Boxes (SDB). From the results of this study, it can be concluded that the factors that cause the loss of valuable objects belonging to customers that are stored in the Safe Deposit Box are the factor of not applying the precautionary principle, the factor of not applying the principle of knowing customers, and the factor of not applying the principle of bank secrecy by the bank. The responsibility of the bank for the loss of valuable objects belonging to customers stored in the Safe deposit box is that the bank is obliged to provide compensation to its customers as a result of their mistakes and omissions that do not apply banking principles. Efforts made by customers for the loss of valuable objects stored in Safe deposit boxes are to propose dispute resolution efforts in the form of non-litigation efforts (outside court) by means of mediation, adjudication, arbitration at alternative dispute resolution institutions (LAPS) in the financial services sector and other efforts litigation (through the court) by filing a lawsuit against the law to the district court.Keywords: Bank, Safe Deposit Box, Customer